2013
DOI: 10.1159/000346682
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia-Induced Neuroinflammation Is Associated with Disrupted Development of Oligodendrocyte Progenitors in a Model of Periventricular Leukomalacia

Abstract: Microglial activation in crossing white matter tracts is a hallmark of noncystic periventricular leukomalacia (PVL), the leading pathology underlying cerebral palsy in prematurely born infants. Recent studies indicate that neuroinflammation within an early time window can produce long-lasting defects in oligodendroglial maturation, myelination deficit, as well as disruption of transcription factors important in oligodendroglial maturation. We recently reported an ischemic mouse model of PVL, induced by unilate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 61 publications
3
47
0
2
Order By: Relevance
“…A proinflammatory state during the perinatal period can already affect oligodendrocyte precursors and elicit cerebral white matter damage and behavioral deficits, as shown in animal models [58,59,60,61,62,63,64]. However, in a control group we injected LPS (0.5 mg/kg) intraperitoneally without induction of HI, but we did not observe any aberrations in cerebral gray or white matter structures or tissue loss in our neonatal mouse model.…”
Section: Discussionmentioning
confidence: 56%
“…A proinflammatory state during the perinatal period can already affect oligodendrocyte precursors and elicit cerebral white matter damage and behavioral deficits, as shown in animal models [58,59,60,61,62,63,64]. However, in a control group we injected LPS (0.5 mg/kg) intraperitoneally without induction of HI, but we did not observe any aberrations in cerebral gray or white matter structures or tissue loss in our neonatal mouse model.…”
Section: Discussionmentioning
confidence: 56%
“…21 In response to an immune activation, microglial cells and astrocytes in the fetal and newborn brain can secrete cytokines such as IL1β and TNFα, causing injury to developing oligodendrocytes and neuronal progenitors. [31][32][33][34] Similarly, studies have demonstrated the presence of hypertrophic astrocytes in kittens and fetal sheep following LPS injection. 35,36 Diffuse astrogliosis is a major pathological feature in white matter injury and is associated with arrest of oligodendrocyte maturation.…”
Section: Glial Activation and Neonatal Brain Injurymentioning
confidence: 92%
“…For quantification of CC1+ oligodendrocytes, ROIs were manually selected in the corpus callosum, external capsule, internal capsule, and hippocampal fimbriae in a posterior section in both the ipsilateral (right) and the contralateral (left) hemisphere. Cell counts per area were measured using MCID Core as previously published [5]. …”
Section: Methodsmentioning
confidence: 99%
“…Apoptosis measured by caspase 3 staining was almost exclusively limited to OPCs within the white matter tracts [15]. Furthermore, we have also shown immediate up-regulation of proinflammatory cytokines [5]. The results of our previous studies suggest that unilateral ischemia leads to a bilateral dysfunction of axons presumably caused by impaired oligodendroglial support.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation